(untitled) (Web of Teachers: Inderscience Research, 2026)
In recent decades, English has become the dominant international language of science and medicine (Crystal, 2003; Montgomery, 2013). Medical professionals rely heavily on English to access scientific literature, publish research findings, participate in international conferences, and collaborate globally to remain updated with advances in healthcare. Consequently, Medical English has become an essential component of medical education, particularly in non-English-speaking countries where students must bridge the gap between local instruction and global scientific communication (Ferguson, 2007; Flowerdew & Peacock, 2001).